An observational study of evaluation of extended first trimester screening test to predict early preterm pre-eclampsia in pregnant women - Parthasarathy K. K. A., Akshaya; J., Madhumitha; Manohar, Sumana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Pre-eclampsia is hypertensive disorder with several complications. Contributes to increased maternal mortality and morbidity. Pre-eclampsia is associated with pre term labour, IUGR and several other complications like end organ failure in mother. So, it is important to diagnose early and take appropriate steps to mitigate maternal mortality and morbidity. Aim was to detect and predict early preterm pre-eclampsia using extended first trimester screening test in pregnant women. Objectives were to assess the sensitivity and specificity of extended first trimester screening test to predict development pre-eclampsia in pregnancy. Methods: Method used in this study was observational study. Results: All three parameters, PAPPA, mean arterial pressure (MAP) and uterine artery pulsatility index found to be significantly associated in predicting early preterm preeclampsia Conclusions: This screening test enables us to predict preeclampsia before its clinical presentation. It can be used as a reliable and a cost-effective screening test. This will help prevent the progression of the disease by taking necessary timely interventions such as ecosprin administration, close and frequent follow up of screen positive mothers. Thus, it is useful tool in reducing the burden of maternal and fetal morbidity on the health system. This study also has confounding factors due to starting of prophylactic treatment with ecosprin based on ACOG/ NICE guidelines, which increased false positive rate.